The Challenging Role of Informal Carers Within the Long-Term Care System in Japan: Focusing on Issues of Japanese Working Carers - Yamaguchi, Mai (Socialinė teorija, empirija, politika ir praktika, 2023)
Despite the increasing demand for long-term care (LTC) caused by demographic changes and several long-term care insurance (LTCI) program reforms, formal care in Japan is shrinking because of public financial constraints, leading to many problems for informal carers. Because more than half of the informal carers are employed in paying jobs, balancing working and caregiving roles is an important issue in the political agenda. Based on an online survey data of working carers of care recipients eligible for the LTCI program (N=600), this study aims to examine informal carers’ challenging role within the Japanese LTC system, and analyze the work-life balance issues of working carers. The results reveal that most of the respondents are their parents’ carers and more than half co-reside with the care-recipients. With the community promoting comprehensive care, many frail older adults now use a combination of formal and informal care services. Additionally, over three hours of informal caregiving per day, age, marital status, co-residence with the care recipient, self-rated health, and insufficient understanding of the caregiving role in the workplace are significantly related to the psychological well-being of informal carers. Furthermore, most of the aforementioned factors are also associated with turnover intention due to caregiving responsibilities. Informal care is a crucial component of the Japanese LTC system and to alleviate informal working carers’ struggles and decrease unwanted turnover, it is necessary to consider the link between formal and informal care, together with support programs for informal carers.